2020
DOI: 10.7759/cureus.8066
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease and New-Onset Atrial Fibrillation: Two Cases

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in a considerable amount of morbidity and mortality worldwide since December 2019. Patients with coronavirus disease (COVID-19) most commonly present with respiratory manifestations, while cardiac manifestations were reported as a complication and seldom as a presenting feature. We report two cases of new-onset atrial fibrillation occurring in middle-aged men with no significant past medical history. The first patient presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 5 publications
2
23
0
1
Order By: Relevance
“…However, reliable data regarding first-diagnosed AF in patients with COVID-19 are limited. Based on case reports [19] , [20] and small clinical studies [21] , [22] , [23] , [24] , new-onset AF varies between 3.6% and 6.7% in patients with COVID-19.…”
Section: Prevalence Of Af In Patients With Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…However, reliable data regarding first-diagnosed AF in patients with COVID-19 are limited. Based on case reports [19] , [20] and small clinical studies [21] , [22] , [23] , [24] , new-onset AF varies between 3.6% and 6.7% in patients with COVID-19.…”
Section: Prevalence Of Af In Patients With Covid-19mentioning
confidence: 99%
“…While atrial structural remodeling is important in providing the AF-maintaining substrate, AF onset and its paroxysms are often temporally related to acute COVID-19 infections. Of note, COVID-19 patients developing AF were older and most of them had at least one preexisting risk factor, including hypertension [19] , [23] , while some did not report any illness. [19] , [20] , [27] Older age and occurrence of heart failure were also associated with greater likelihood of incident AF during the COVID-19 infection [21] .…”
Section: Mechanisms Of Af In Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…AF is the most common arrhythmia noted among elderly individuals [ 17 ]. Although, earlier new onset AF is rare [ 18 ], it helps predict disease severity and mortality [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of arrhythmias and conduction system disease in patients with COVID-19 varies from population to population [4]. Several case reports have shown that onset of atrial fibrillation may vary from a few days up to a week from acquiring the infection; however, sometimes may be longer [5,6]. Regarding the mechanism, hypoxia and electrolyte abnormalities, both known to contribute to the development of acute arrhythmias, have been frequently reported in the acute phase of COVID-19 illness [4].…”
Section: Introductionmentioning
confidence: 99%